Health of children born to medical radiographers. Issue 2 (February 1996) - Roman, E; Doyle, P; Ansell, P; Bull, D; Beral, V
Abstract : OBJECTIVES: To develop a reliable method for collecting information on reproductive outcome in an occupational setting; and to investigate the health of children born to medical radiographers. METHODS: The study population comprised 6730 members of the College of Radiographers who were, at the time of survey; aged between 30 and 64 years, on the current membership file of the College, and were resident in Britain. RESULTS: The postal method developed proved to be reliable, with around 87% of questionnaires being returned. The observed frequencies of reproductive events were broadly in line with findings from other studies: of the 9208 pregnancies reported, 83% were livebirths, 12% were miscarriages (gestational age < 20 weeks), 1% were stillbirths (gestational age > or = 20 weeks), and 1% were other rarer spontaneous adverse events (ectopic pregnancy, blighted ovum, and hydatidiform mole). There was little difference between men and women in the frequency of adverse reproductive events reported, with the exception that male radiographers reported fewer medical terminations, the proportions being 3.1% and 1.4% for women and men respectively. Among children, the overall risks of major congenital malformation (RR 1.0, 95%CI 0.9-1.2), chromosomal anomaly (RR 1.4, 95%CI 0.8-2.3), and cancer (RR 1.2 95%CI 0.7-2.0) were as expected based on general population rates. Borderline excesses of chromosomal anomalies other than Down's syndrome in the children of female radiographers (RR 3.9, 95%CI 1.3-9.0, based on five observations), and cancer in the children of male radiographers (RR 2.7, 95%CI 0.9-6.5, based on five observations) were noted. The numbers on which these risks are based are small and the findings should be interpreted cautiously. CONCLUSIONS: The postal methods developed for obtaining information about reproductive events and child health proved to be reliable in men, as well as in women. Overall, the findings for medical radiographers are reassuring. Dose-response relations could not, however, be examined as long term dose records of radiographers are not routinely kept in an accessible form.